1999
DOI: 10.1159/000023425
|View full text |Cite
|
Sign up to set email alerts
|

Management of Males with 45,X/46,XY Gonadal Dysgenesis

Abstract: Males with the 45,X/46,XY karyotype and malformations of the external genitalia carry an increased risk of developing germ cell neoplasia of the gonads. We have studied gonadal tissue from 10 individuals, 0.3–17 years of age, with a male phenotype and either hypospadias and/or cryptorchidism. Four patients, 0.3–15 years of age, had carcinoma in situ, 1 boy had Sertoli-cell-only pattern and the remainder prepubertal histology. Gonadoblastoma or invasive carcinoma was not found. On the basis of our current knowl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
28
0
1

Year Published

2001
2001
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(30 citation statements)
references
References 31 publications
(23 reference statements)
1
28
0
1
Order By: Relevance
“…The possibility of testicular biopsy after puberty should be strongly considered in 45,X/46,XY males with cryptorchism and/or hypospadias. 9,10 The growth pattern of 45,X/46,XY female and male children recently described by Tosson et al revealed growth deceleration at the time of puberty and adult height compromised relative to mid-parental height. 7 Early GH treatment should be considered to be part of the management of short stature in 45,X/46,XY male children because, like girls with Turner syndrome, a good linear growth response to GH therapy was observed in these boys who started GH therapy early in life.…”
Section: Case Reportmentioning
confidence: 97%
See 1 more Smart Citation
“…The possibility of testicular biopsy after puberty should be strongly considered in 45,X/46,XY males with cryptorchism and/or hypospadias. 9,10 The growth pattern of 45,X/46,XY female and male children recently described by Tosson et al revealed growth deceleration at the time of puberty and adult height compromised relative to mid-parental height. 7 Early GH treatment should be considered to be part of the management of short stature in 45,X/46,XY male children because, like girls with Turner syndrome, a good linear growth response to GH therapy was observed in these boys who started GH therapy early in life.…”
Section: Case Reportmentioning
confidence: 97%
“…Tumor risk is significantly higher in patients with marked genital ambiguity as compared to patients with mild undervirilisation or with a female phenotype. 1,9,10 There is not an exact prediction of tumor risk in normal males with 45,X/46,XY constitution, but based on the study of Cools et al, the risk is low because the clinical picture of a normal external masculinisation score and bilaterally descended testes suggests a (close to) normal testicular differentiation and maturation process. 9 Although our patients belong to the lower tumor risk category, close follow-up for development of gonadal tumors is mandatory, including physical examination and laboratory investigation with ultrasonography and serum tumor markers.…”
Section: Case Reportmentioning
confidence: 99%
“…Follow up of 92 patients in whom this karyotype had been detected by antenatal testing revealed that 95% had a normal male phenotype and of these, 27% had abnormal gonadal histology [Chang et al, 1990]. The risk of malignancy in the group with male phenotype remains unclear; a strategy has been proposed for management, involving close monitoring and testicular biopsies after puberty has been completed [Müller et al, 1999].…”
Section: X/46xy Partial Gonadal Dysgenesismentioning
confidence: 99%
“…liczbowe i strukturalne aberracje chromosomów płciowych [24,25]. Przypuszcza się także, że TDS może być związany z występowaniem specyficznej haplogrupy chromosomu Y -hp26, która jest najczęściej stwierdzana w populacji duńskiej i być może jest szczególnie wrażliwa na czynniki środo-wiskowe.…”
Section: Patogeneza Tdsunclassified